Asymmetric Adjustment between Oil Prices and the Consumer Price Index in Malaysia: Evidence from Aggregated and Disaggregated Levels - Tan, Yan-Ling; Habibullah, Muzafar Shah; Yiew, Thian-Hee (Panoeconomicus, 2025)
This study examines the asymmetric adjustment of the consumer price index in Malaysia in response to changes in oil prices from January 2005 to December 2022, at both aggregated and disaggregated levels. The findings of momentum threshold autoregressive cointegration tests indicate a cointegrating relationship between oil prices and the consumer price index in Malaysia. The consumer price index and its subcategories demonstrate varying speeds of adjustment back to equilibrium. Specifically, the aggregated consumer price index and the majority of the disaggregated consumer price indexes adjust relatively quickly back to equilibrium when oil prices fall, as opposed to when they rise. This suggests that the pass-through effect of oil prices on consumer prices is heterogeneous, with significant variations in the speed of adjustment across different consumer price subcategories. Consequently, these adjustment speeds should not be overlooked when considering the direction of monetary policy. JEL: C22 E31 Q43